Regional urban studies as a promising trend in Kazakhstan linguistics - Suyunova, Gulnara; Andryuchshenko, Olga (Przegląd Wschodnioeuropejski, 2017)
s, including the use of urbonymic systems from the point of view of their communicative existence. Urbonymes, their typology, linguistic analysis of functioning of systems of Kazakhstan cities-related onomastic terms are promising issues of Kazakhstan’s Russian studies. The authors emphasize the close relation of onomastic processes to the society life. The formation of onomastic space of independent Kazakhstan and the definition of its national expression are considered by the researchers as one of the most important problems of the modern Kazakhstan linguistics. Language planning and language policy should become an integral part of a general policy aimed at improving the social, economic and cultural situation in the city. This provision is significant for the nomination process in Pavlodar, the onomastic system of which, like of a similar system of any Kazakhstan city, reflects the sociocultural changes taking and having already taken place. The article specifically shows promising new approaches to the study of the city, in particular, from the standpoint of study of general cultural landscape of the city.